Potentiometric Carbon Quantum Dots-Based Screen-Printed Arrays for Nano-Tracing Gemifloxacin as a Model Fluoroquinolone Implicated in Antimicrobial Resistance - Miriam F. Ayad; Yossra A. Trabik; Mona H. Abdelrahman; Nermine V. Fares; Nancy Magdy (Chemosensors, 2020)
Antimicrobial resistance (AMR) is a neglected issue that poses a serious global threat to public health, causing long-term negative consequences at both humanitarian and economic levels. Herein, we report an unprecedented economic fabrication method of seven potentiometric screen-printed sensors for the ultra-trace determination of gemifloxacin (GEMI) as a model of the fluoroquinolones antibiotics deeply involved in the growing AMR problem. Sensors were constructed by depositing homemade carbon ink on a recycled X-ray sheet, patterned using stencils printed with an office printer in simple, cost-effective steps requiring no sophisticated equipment. Four sensors were modified using carbon quantum dots (CQDs) synthesized from dextrose through a single-step method. Sensors exhibited a linear response in the concentration ranges 10−5–10−2 M (sensors 1, 3 and 4), 10−6–10−3 M (sensor 2) and 10−6–10−2 M (sensors 5, 6 and 7). LOD allowed tracing of the target drug at a nano-molar level down to 210 nM. GEMI was successfully determined in pharmaceutical formulations and different water samples without any pretreatment steps with satisfactory recovery (96.93–105.28% with SD values < 3). All sensors revealed a long lifetime of up to several months and are considered promising tools for monitoring water quality and efficiency of water treatment measures.